Ultrasound diagnostics of left ventricular noncompaction - A. O. Barakin; L. V. Bregel; V. M. Subbotin; O. S. Efremova (Acta Biomedica Scientifica, 2017)
The clinical cases of rare, genetically heterogeneous cardiomyopathy are described - the left ventricular noncompaction (LVNC) cardiomyopathy for four children (three boys and one girl) in age from two months to 6 years. Description of echocardiography signs is presented in accordance with modern diagnostic criteria. Noncompaction of the left ventricle is recognized in three patients, of the left and right ventricle - in one. In three patients out of four, LVNC was a separate disease, and yet in one it was associated with neurofibromatosis type 1, in combination with dilatation of coronary arteries and pericardial effusion. Three of four patients were admitted with congestive heart failure (CHF) of New York Heart Association (NYHA) functional class 3-4 (FC), and one - with CHF 2 FC. The echocardiograms are brought with description of characteristic features of LVNC (hypertrabecularity, spongy myocardium on the apex of the left ventricle, typical correlation of incompact and compact layer from 2.0 to 2.6). All four patients received treatment for CHF (diuretics, beta-blockers, captopril, in one case - digoxin); two out of four got antithrombotic therapy (aspirin, warfarin). Results of follow-up observation of the patients are described with the estimation of echocardiography signs, including dilatation of coronary arteries. Left ventricular ejection fraction - both by Simpson and Teicholz - increased in two patients, with therapy of chronic heart failure at a follow-up visits over > 5 years simultaneously with the decline of severity of CHF. Another two patients have been examined from 2 months to 5 years and have had CHF 3 FC; their left ventricular ejection fraction increased too, but cardiomegaly and right ventricular heart failure preserved.